Enhancing SME performance through innovation: evidence from a transition economy – Kosovo - Mulolli, Enis; Islami, Xhavit; Hashani, Medain (Business, Management and Economics Engineering, 2024)
Purpose – What are the effects of implementing various types of innovation, including product, process, and technological innovations, on the performance of SMEs in the manufacturing sector? This is a question that preoccupies us a lot. This study seeks to examine the individual and integrated effects of these innovations. Indeed, we examine the impact of three categories of innovation – product, process, and technological innovation – on the performance of SMEs in the manufacturing industry. Research methodology – We used a quantitative approach to execute this research, selecting SMEs at random using self-administered questionnaires. The data collected from 153 manufacturing SMEs was analyzed using hierarchical linear regression to investigate, evaluate, and refine the relation among product, process, and technological innovation and SME performance. Findings – This study’s findings reveal a clear and direct relationship between these three forms of innovation and SMEs’ performance. This study also provides empirical evidence that various forms of innovation, either examined individually or as integrated, exert a positive effect on the performance of SMEs in the manufacturing industry. Limitations – This study focuses on Kosovo-based SMEs, with the assumption of an upright connection between variables. Future studies can examine the existence of reverse causality in a variety of regional, cultural, and industrial settings. Originality/Value – This study significantly advances existing knowledge by providing useful insights into the complex interplay among product, process, and technological innovation (examined from both individual and integrated perspectives) as well as the performance of SMEs in the manufacturing industry.